Det paradoksale sprog i Erasmus af Rotterdams Dårskabens lovprisning - Johansen , Theis Schønning (Dansk Teologisk Tidsskrift, 2024)
Erasmus of Rotterdam’s The Praise of Folly is a highly original paradoxical encomium in that the praise is undertaken by Folly herself. In his insightful work, Günter Bader points out the structural importance and theological consequences of this second-degree paradox in Folly’s self-praise, from which this article has drawn inspiration in order to understand among other things the complexity of the role of language and words in relation to the cognition of things in The Praise of Folly. This complexity undoubtedly pertains to other works in the opus of Erasmus, as is shown in the article, which forces us to reconsider our reception and interpretation of Erasmian Christology, Pneumatology and anthropology.